Staphylococcus aureus Isolated from the Oral Cavity: Phage Susceptibility in Relation to Antibiotic Resistance - Katarzyna Garbacz (MDPI AG, 2021)
Nowadays, research on bacteriophage therapy and its potential use in combination with antibiotics has been gaining momentum. One hundred and ten oral Staphylococcus aureus isolates were phage-typed and their antibiotic resistance was determined by standard and molecular methods. The prevalence of MSSA and MRSA strains was 89.1% and 10.9%, respectively. Nearly all (91.8%) analyzed isolates, whether MSSA or MRSA, were susceptible to the phages used from the international set. The highest lytic activity showed phages 79 and 52 A from lytic group I. The predominant phage groups were mixed, the I+III group and a mixed group containing phages from at least three various lytic groups. S. aureus strains sensitive to phage group I were usually resistant to penicillin and susceptible to ciprofloxacin, whereas the strains typeable with group V or group V with the 95 phage were susceptible to most antibiotics. Epidemic CA-MRSA strains (SCCmecIV) of phage type 80/81 carried Panton–Valentine leucocidin genes. Considering the high sensitivity of oral S. aureus to the analyzed phages and the promising results of phage therapies reported by other authors, phage cocktails or phage-antibiotic combinations may potentially find applications in both the prevention and eradication of staphylococcal infections.